Statics (Springer, 2009)
The book is the first of three volumes on engineering mechanics. It is intended for engineering students of universities and colleges, and contains basic concepts and principles of mechanics/statics in simple and convenient form. Numerous exercises (and their solutions) allow the students to reduce the gap between theoretical models of analytical mechanics and needs of engineering. The content of the volume is traditional